Kisah Di Balik Hujan : Pemahaman Anak-Anak Tentang Fenomena Cuaca dalam Pembelajaran IPAS di MIS Wonoyoso - Dian ika Safitriana (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2025)
This research aims to explore how a story-based learning approach can increase students' understanding of the rain phenomenon in Natural and Social Sciences (IPAS) learning at the elementary school level. Using a qualitative approach and case studies, this research involved fourth grade students and science and science teachers in one elementary school. The research results show that story-based learning is able to change students' erroneous understanding of the rain phenomenon into a more accurate scientific understanding. Stories that connect scientific concepts with students' daily experiences successfully increase their engagement and participation in learning. In addition, this approach can also simplify abstract concepts such as the water cycle, making the material more interesting and easy to understand. Despite some challenges, such as the time required to design relevant stories, the positive impact of this approach on students' understanding and their engagement is significant. It is hoped that this research can contribute to the development of more creative and contextual science learning methods in elementary schools.